Pengaruh Media Kompos Abu Sabut Kelapa terhadap Pertumbuhan Vegetatif Tanaman Cabai Rawit (Capsicum frustescens) - Anggraini, Aulia; Sukri, Akhmad; Masiah, Masiah (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2022)
The availability of nutrients in the growing media greatly affects the process of plant growth. This study aims to determine the effect of coconut coir compost media on the vegetative growth of cayenne pepper (Capsicum frustescens). This research was carried out at the Green House of the Department of Biology Education, Faculty of Applied Science and Engineering, Mandalika University of Education from September 22 - November 2, 2021 and the weighing was carried out at the Biology Laboratory, Faculty of Applied Science and Engineering, Mandalika University of Education. The design of this study used a completely randomized design (CRD) with 4 treatments and 6 replications, namely the treatment of coconut coir ash concentration P1 (coco coir ash concentration 5.0 grams), P2 (10 grams coconut coir ash concentration), P3 (coconut ash concentration 10 grams), P3 (coconut ash concentration 10 grams), coconut 15 grams), and 1 control treatment. Parameters observed were number of leaves, stem height, wet weight, and dry weight. The data obtained were analyzed using Analysis of Variance (ANOVA). The results showed that: 1) there were differences in the number of leaves and stem height for each treatment (P < 0.05), where the highest to lowest number of leaves and stem height were obtained in treatments P0, P1, P2, and P3; 2) there was no difference in wet weight for all treatments (P > 0.05); and 3) there was no difference in dry weight for all treatments (P > 0.05). The practicum guide enrichment materials produced from this study have met the criteria for media validation with a score of 70.83%, content validation 75%, and language validation 65%. With this result, the enrichment material is in the feasible category.